Airline crisis: communication effects on customer engagement during the Covid-19 pandemic 2020 - Panda, Bhagyashree (2021)
Customer Engagement refers to emotional attachment that customer experiences with the service provider during the repeated communication and ongoing interactions during the service. Engagement occurs through satisfaction, loyalty and excitement about the company (Hollebeek, Srivastava and Chen's, 2019).